Ephedrine Infusion Prevents Hypotension and Reduces Nausea in Cesarean Section Under Spinal Anesthesia: Infus Efedrin Mencegah Hipotensi dan Mengurangi Mual pada Operasi Caesar dengan Anestesi Tulang Belakang - Maha Sabri Younis; Sumaya Alwan Salman; Eahab Nabeel Khamees (Universitas Muhammadiyah Sidoarjo, 2024)
In this study, we aimed to evaluate the efficacy of ephedrine infusion in preventing hypotension and minimizing nausea in healthy pregnant women undergoing elective cesarean sections with spinal anesthesia. Forty-four participants were included, with 20 receiving ephedrine infusion and 24 serving as controls receiving bolus injections. Results revealed a significant reduction in the incidence of hypotension (p > 0.1) and nausea (p < 0.001) in the infusion group compared to the controls. No instances of reactive hypertension were observed in the infusion group. Other variables including Apgar scores, fetal blood gas tensions, and onset of respiration remained comparable between the groups. These findings suggest that ephedrine infusion is not only safe but also preferable in mitigating adverse events during cesarean sections under spinal anesthesia in normal pregnancies. Highlights: Ephedrine infusion effectively prevents hypotension during cesarean sections under spinal anesthesia. Administration of ephedrine infusion significantly reduces the incidence of nausea compared to bolus injections. No instances of reactive hypertension were observed in patients receiving ephedrine infusion, highlighting its safety profile in this context. Keywords: Ephedrine Infusion, Cesarean Section, Spinal Anesthesia, Hypotension Prevention, Nausea Reduction